Defrocking the false father of the 'Driftless Area', USA. (29th March 2023) - Brick, Greg
Abstract : The Driftless Area is a designation popular in American promotional tourist literature for an area in four contiguous American states, Minnesota, Wisconsin, Iowa and Illinois, that were not glaciated during the latest ice advance. Geographer Lawrence Martin published several articles asserting that geologist William H. Keating first discovered this area in 1823, an error that has crept into subsequent accounts. But historical evidence goes to show that three geologists, Roland D. Irving, Newton H. Winchell and Thomas C. Chamberlin, were simultaneous originators of the concept as we understand it today, about the year 1877.